Acupuncture for mild cognitive impairment: A systematic review with meta-analysis and trial sequential analysis - Yin, Zihan; Li, Yaqin; Jiang, Cheng; Xia, Manze; Chen, Zhenghong; Zhang, Xinyue; Zhao, Ling; Liang, Fanrong (Frontiers in Neurology, 2023)
Background: The evidence of acupuncture for mild cognitive impairment (MCI) is insufficient, and there is no consensus regarding its efficacy. This review aims to determine acupuncture effect in patients with mild cognitive impairment. Methods: Relevant potentially eligible randomized controlled trials (RCTs) about acupuncture for MCI were obtained from four Chinese databases, four English databases, and additional resources until 1st August 2022. The primary outcome was the improvement of overall cognitive function (OCF). Secondary outcomes included improved memory function (MF) and activity of daily living (ADL). The revised Cochrane collaboration risk of bias assessment tool (ROB 2.0) was applied to evaluate the methodological quality. The Review Manager software v 5.4 were implemented for analyses. Trial sequential analysis (TSA) 0.9.5.10 β software was employed to estimate the required sample size and test the reliability of the pooled outcome. The quality of evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) tool. Results: This meta-analysis included 11 RCTs with a total of 602 patients. All trials’ methodological quality was moderate. Low quality of evidence showed that acupuncture significantly improved the OCF (Mini-mental State Examination; mean difference (MD) 1.22, 95% confidence interval (CI): 0.78 to 1.66; Montreal Cognitive Assessment Scale; MD 1.22, 95% CI: 0.47 to 1.97). In subgroup analyses, it revealed that acupuncture significantly increased the OCF of MCI in patients between conventional medicine as well as sham acupuncture. Findings from the TSA suggested that the evidence of improving OCF on acupuncture for MCI in patients was conclusive. Meanwhile, there is no statistical difference between acupuncture and conventional medicine in improving MF and ADL. TSA showed that the evidence of improving MF and ADL on acupuncture for MCI in patients receiving acupuncture was inconclusive. The shreds of evidence of improving MF and ADL were ranked as low to critically low. Conclusion: Acupuncture appears to be an effective method for clinical application for overall cognitive function improvement in MCI patients. However, due to the low evidence, more relevant high-quality research in this field is needed. Systematic review registration: PROSPERO, No. CRD42021291284.